Universalism and particularism at Sodom and Gomorrah: essays in memory of Ron Pirson - Lipton, Diana; Pirson, Ron (Ancient Israel and its literature / Society of Biblical Literature, 2012)
Remembering Ron Pirson, by his life-partner / Petra Thijs -- Ron Pirson: memories of a former colleague / Pierre Van Hecke -- Ron Pirson: publications -- The eternal liminality of Lot: paying the price of opposing the particular in the Sodom narrative / William John Lyons -- The limits of intercession: Abraham reads Ezekiel at Sodom and Gomorrah / Diana Lipton -- Changing God's mind: Abraham versus Jonah / T. A. Perry -- Why did God choose Abraham? Responses from medieval Jewish commentators / Amira Meir -- Outcry, knowledge, and judgment in Genesis 18-19 / Ellen J. Van Wolde -- Legal and ethical reflections on Genesis 18 and 19 / Calum Carmichael -- Keeping the way of YHWH: Righteousness and justice in Genesis 18-19 / Megan Warner -- Was Lot a good host? Was Lot saved from Sodom as a reward for his hospitality? / Yitzhak (Itzik) Peleg -- Hospitality compared: Abraham and Lot as hosts / Jonathan D. Safren -- Hospitality and hostility: reading Genesis 19 in light of 2 Samuel 10 (and vice versa) / Nathan MacDonald -- Beyond particularity and universality: reflections on Shadal's commentary to Genesis 18-19 / Harlan J. Wechsler -- Does Lot know about Yada'? / Ron Pirson